Factors Affecting the Results of Superficial Femoral Artery Stenting. (November 2015) - Kay, Mark; Rogoveanu, Radu; Hodson, James; Tallowin, Simon; Hopkins, Jonathan; Duddy, Martin; Vohra, Rajiv
Introduction: The aim of this study was to assess the durability of superficial femoral artery (SFA) stents and factors that affect stent patency. Methods: A retrospective assessment of 214 SFA stent procedures between 2003 and 2012 was conducted from a prospectively compiled database. Patency rates and patient outcomes were compiled from case notes and computerized records. Stent patency was confirmed by either duplex scan or clinical examination (palpable distal pulse). Survival and patency were compared across a range of factors using Kaplan-Meier plots and log-rank tests. Factors found to be significant were further assessed by Cox regression models. Results: Data were analyzed for 214 limbs in 205 patients. Inclusion criteria included those patients who received an SFA stent for treatment of claudication or critical limb ischemia (CLI) with follow-up data. This gave a study group of 151 limbs divided into 76 claudicant and 75 patients with CLI (male–female ratio = 103:48, mean age 71 years, standard deviation 11.7). Seventy-one percent of procedures were elective and 29% were emergency procedures; 53% of procedures were carried out on a day case basis. Median follow-up was 11 months (range 1 day-89 months). Patency was significantly worse for patients with CLI ( P = .009), with a 1- and 3-year patency of 63% and 34% compared to 79% and 60% in patients with claudication. Significant factors associated with patency included oral therapy controlled diabetes ( P = .003), lesions located in either the mid-SFA ( P = .029) or the mid-popliteal ( P = .013), and periprocedural complications ( P = .005). There was no significant difference in patency rates between insulin-dependent and nondiabetic patients (hazard ratio: 1.0, 95% confidence interval: 0.4-5.6, P = .983). The overall amputation rate for the total study group was 5%. Patients with 1- and 3-year survival were 98% and 96% in the claudication group and 74% and 51%, respectively, in the CLI group. Conclusion: SFA stents have superior outcomes in claudicants. Patency is related to severity of disease, diabetes, and location of disease.